The Relationship Between Characteristics, Intrinsic Motivation, Extrinsic Motivation with Job Satisfaction of Nurses at Royal Prima General Hospital Medan - Sumarlan, Savira Budiarny Putri; Nasution, Siti Khadijah; Juanita, Juanita (Randwick International of Social Science Journal, 2025)
HRD are one of main factors in the organization or association in achieving the goals of the organization. Job satisfaction of nurses is a factor that can affect characteristics, motivation at work, namely intrinsic motivation and extrinsic motivation. Royal Prima Medan General Hospital is an organization engaged in the health sector which has 265 nurses. In managing its quality is in order to create job satisfaction. So that, it will have an impact on performance and service in the hospital. The main objective in this study was to determine the effect of characteristics, intrinsic motivation and extrinsic motivation on nurses' job satisfaction at Royal Prima Medan General Hospital. The research conducted was quantitative research, focusing on observational or measured data expressed in numerical values. The research design used a cross-sectional approach. The research took place at Royal Prima General Hospital Medan from March to October 2024. The population studied consisted of all nurses in the hospital, with a sample size of 100 individuals selected using total sampling due to the large population size. The data analysis method in this study was bivariate using chi- square. The results showed that characteristics have no relationship with nurses' job satisfaction, promotion and job achievement have a significant relationship with job satisfaction, extrinsic motivation has a significant relationship with job satisfaction, namely the job security variable. For Royal Prima Medan General Hospital, it is recommended to provide better promotion, achievement and job security and improve nurses' job satisfaction